(untitled) (ENTHYMEMA, 2011)
Below are the videos of the interview recorded the 21st May 2011 in Fribourg (CH), in occasion of the first RRN conference. Conversation with Meir Sternberg. Part 1 of 8 - Narratology: classical and postclassical studies. Part 2 of 8 - The development of an original theoretical framework. Part 3 of 8 - Sternberg and Genette: different ways for the same problems. Part 4 of 8 - «There are no forms except in terms of functions». Part 5 of 8 - A life writing articles: so many papers and just four books. Part 6 of 8 - Two arguments against mimetical approaches to narrative. Part 7 of 8 - «Narrative is not given, it is a construct». Part 8 of 8 - The proteus principle. the many-to-many correspondence between forms and functions.